2018
DOI: 10.3389/fphar.2018.00737
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Induces Endothelial-to-Mesenchymal Transition-Like Phenotypic Switching

Abstract: Valproic acid (VPA), a histone deacetylase (HDAC) inhibitor, is a widely used anticonvulsant drug that is currently undergoing clinical evaluation for anticancer therapy due to its anti-angiogenic potential. Endothelial cells (ECs) can transition into mesenchymal cells and this form of EC plasticity is called endothelial-to-mesenchymal transition (EndMT), which is widely implicated in several pathologies including cancer and organ fibrosis. However, the effect of VPA on EC plasticity and EndMT remains complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 104 publications
(145 reference statements)
1
28
0
Order By: Relevance
“…Accordingly, we plan to evaluate the potential role of the drug VPA on ACE-2 expression in ECs. We also discuss our findings in relation to other published articles [19], providing a plausible mechanism for the use of VPA for the prevention and treatment of COVID-19 ( Figure 2).…”
Section: Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…Accordingly, we plan to evaluate the potential role of the drug VPA on ACE-2 expression in ECs. We also discuss our findings in relation to other published articles [19], providing a plausible mechanism for the use of VPA for the prevention and treatment of COVID-19 ( Figure 2).…”
Section: Methodssupporting
confidence: 68%
“…To test our hypothesis, we evaluated ACE-2 expression in cultured HUVECs that were treated with clinically relevant dose (5 mM) of VPA [19,21] for 24 hours. HUVECs represent the standard cellular model to study endothelial cells in vitro [19,20,22]. Our qPCR data demonstrated a significant ~70% reduction (p = 0.0079) in the expression level of ACE-2 in VPA-treated ECs in comparison to control ECs ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Densitometry (ImageJ software) was performed to quantify the band intensities. Immunofluorescence experiments were carried out in 4-chamber microscopy slides performed as previously described 33,48,49 . Immunofluorescence signals from Acetyl-tubulin, CD31, VE-Cadherin, αSMA, Ift88 and α-actinin staining were visualized with standard protocols 24 hours post-treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Responses to cancer treatment have important issues, leading to efficiency but often to resistance. Cancer therapies such as conventional radiotherapies (Mintet et al, 2015;Choi et al, 2018), high-dose radiation therapies (Banerjee et al, 2020) but also chemotherapies (Murugavel et al, 2018) are also currently identified as promoting EndMT in diverse type of tumors, with consequences in tumor response as described below.…”
Section: Source Of Cafsmentioning
confidence: 99%